PRACTICAL APPLICATION OF DIGITAL SERVICES IN SOCIAL PROTECTION ACROSS REGIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid expansion of digital technologies has significantly transformed social protection systems, particularly in the way social services are delivered and accessed at the subnational level. In many countries, the practical application of digital social protection services varies considerably across regions due to differences in institutional capacity, digital infrastructure, governance arrangements, and socio-economic conditions. This article examines the practical implementation of digital services in social protection across regions, with a specific focus on district- and local-level delivery mechanisms. Using a system-based and process-oriented analytical framework, the study explores how digital tools such as integrated social registries, management information systems (MIS/SPIS), government-to-person (G2P) digital payments, and grievance redress mechanisms are applied in different territorial contexts. The analysis highlights regional disparities in service coverage, targeting accuracy, delivery speed, and user experience, as well as the institutional and technological factors shaping these outcomes. The findings indicate that regions with higher levels of inter-agency integration, data interoperability, and digital capacity achieve more effective and inclusive social protection outcomes. At the same time, digital divides, uneven infrastructure development, and limited digital literacy continue to constrain the effectiveness of digital services in less developed regions.